Critical Analysis Hadith of War: Between Historical Context and Contemporary Relevance - Muhammad Raqib Assidiqi (Yayasan Pesantren Mahasiswa An-Nur, 2023)
Perceptions that associate Islam with acts of violence have been the subject of protracted debate. This article delves deeper into this issue while emphasizing the significance of analyzing the historical context and interpretation of religious texts. The research adopts the methods of talāzum and al-takhrīj to interpret the traditions to understand their meaning and integrity. By detailing the understanding of the traditions of jihad in Islam, it can be asserted that the act of killing can only be justified in the context of war and self-defense. This understanding is critical to clarifying false claims regarding the use of violence in Islam. A concrete example of the justified understanding can be seen in the decisive action taken by Abu Bakr in the face of rebellion. However, in the contemporary era, acts of radicalism that involve killing clearly contradict the concept of jihad presented by the scholars of Ahl al-Sunnah. It also violates the law, humanitarian principles, and ethics. This article discusses why educative approaches and intercultural dialog are considered more effective solutions for countering extremism and achieving peace in a diverse global society.